Role of defects and their complexes on the dependence of photoconductivity on dark resistivity of single ZnO microwires - Villafuerte, Manuel José (2017)
We have studied the correlation between the photoconductivity and the dark resistivity of single ZnO microwires. We found that as-grown microwires with higher dark resistivities have higher photoconductivities. However, when the microwires are thermal treated in vacuum, this correlation is inverted. We have also analyzed the behavior of photoconductivity on protonated as-grown samples. We discuss the origin of these behaviors in terms of the interplay of oxygen and zinc vacancies and their complexes acting as recombination or trapping centers.